Prevalence and determinants of Leishmania major infection in emerging and old foci in Tunisia - Jihene Bettaieb; Amine Toumi; Sadok Chlif; Bilel Chelghaf; Aicha Boukthir; Adel Gharbi; Afif Ben Salah (Parasites & Vectors, 2014)
Abstract Background Zoonotic Cutaneous Leishmaniasis (ZCL) due to Leishmania major (L. major) is still a serious public health problem in Tunisia. This study aimed to compare the prevalence and risk factors associated with L. major infection in old and new foci using leishmanin skin test (LST) in central Tunisia. Methods A cross sectional household survey was carried out between January and May 2009 on a sample of 2686 healthy individuals aged between 5 and 65 years. We determined the prevalence of L. major infection using the LST. Risk factors of LST positivity were assessed using a logistic regression model. Results The overall prevalence of LST positivity was 57% (95% CI: 53–59). The prevalence of L. major infection was significantly higher in the old focus (99%; 95% CI: 98–100) than in the emerging foci (43%; 95% CI: 39–46) (p = <0.001). Multivariate analysis of LST positivity risk factors showed that age, the nature of the foci (old/emerging), personal and family history of ZCL are determinants of positive LST results. Conclusion The results updated the current epidemiologic profile of ZLC in central Tunisia. Past history of transmission in a population should be considered as a potential confounder in future clinical trials for drugs and vaccines against L. major cutaneous leishmaniasis.